Designing Safer CRISPR/Cas9 Therapeutics for HIV: Defining Factors That Regulate and Technologies Used to Detect Off-Target Editing - Sullivan, Neil T.; Allen, Alexander G.; Atkins, Andrew J.; Chung, Cheng-Han; Dampier, Will; Nonnemacher, Michael R.; Wigdahl, Brian (Frontiers in Microbiology, 2020)
Human immunodeficiency virus type-1 (HIV-1) infection have resulted in the death of upwards of 39 million people since being discovered in the early 1980s. A cure strategy for HIV-1 has eluded scientists, but gene editing technologies such as CRISPR/Cas9 offer a new approach to developing a cure for HIV infection. While the CRISPR/Cas9 system has been used successfully in a number of different types of studies, there remains concern for off-target effects. This review details the different aspects of the Cas9 system and how they play a role in off-target events. In addition, this review describes the current technologies available for detecting off-target cleavage events and their advantages and disadvantages. While some studies have utilized whole genome sequencing (WGS), this method sacrifices depth of coverage for interrogating the whole genome. A number of different approaches have now been developed to take advantage of next generation sequencing (NGS) without sacrificing depth of coverage. This review highlights four widely used methods for detecting off-target events, (1) genome-wide unbiased identification of double-stranded break events enabled by sequencing (GUIDE-Seq), (2) discovery of in situ Cas off-targets and verification by sequencing (DISCOVER-Seq), (3) circularization for in vitro reporting of cleavage effects by sequencing (CIRCLE-Seq), and (4) breaks labeling in situ and sequencing (BLISS). Each of these technologies has advantages and disadvantages, but all center around capturing double-stranded break (DSB) events catalyzed by the Cas9 endonuclease. Being able to define off-target events is crucial for a gene therapy cure strategy for HIV-1.